The future of wireless communications - Webb, William, 1967- (Artech House, 2001)
Here's a forward-looking new book that realistically forecasts the changes in mobile communications over the next 20 years to help you make informed decisions and develop successful strategies that address the future challenges of this industry. You get specific recommendations on which technological areas organizations should concentrate on, along with insightful discussions on technology and the limits of efficiency, standardization, radio spectrum, economics, industry structure, user requirements, and other constraints and drivers. Publisher abstract.
Keywords: Wireless communication systems.; Transmission sans fil.; TECHNOLOGY & ENGINEERING -- Mobile & Wireless Communications.; Wireless communication systems